INFLUENCE OF ECO-FRIENDLY SPECIAL FINISHES ON NATURALLY COLOURED COTTON IN GREEN TEXTILES - NAMRATA M, (The Journal of Research ANGRAU, 2026)
Eco-friendly textiles are currently in high demand across the industry. Global warming, pollution and other ecological concerns are receiving increasing attention on one hand; on the other, a growing number of consumers are recognizing the need for safe and sustainable fashion. The concept of green textiles encompasses eco-conscious production, sustainable clothing and environmentally responsible fashion—designed to be both safe and secure. Eco-friendly special finishes, including bio-finishes, have emerged as vital enhancements in the textile industry, imparting desirable properties to fabrics while reinforcing the ethos of eco-fashion. In 2021, a study was undertaken to evaluate the influence of specialized eco-finishes on DDCC-1 (Dharwad Desi Coloured Cotton-1) fabric. The fabric underwent bio-desizing to reduce residual sizing agents, followed by bio-polishing to eliminate protruding surface fibers, thereby enhancing smoothness. Subsequently, it was treated with a silicon-based softener to improve its tactile feel and overall comfort. This multi-stage eco-finishing process aimed to elevate both the aesthetic and functional qualities of DDCC-1 in alignment with sustainable textile practices. The control and finished fabrics were evaluated for their mechanical and functional properties, with statistical analysis conducted using the t-test to determine the significance of observed changes. The study revealed that the application of a silicone softener finish notably enhanced the flexibility, drape and pliability of naturally coloured cotton khadi fabric, resulting in improved softness and surface smoothness. Furthermore, tensile strength increased substantially—from 26.00 kgf to 42.88 kgf in the warp direction, and from 15.10 kgf to 25.24 kgf in the weft. These improvements underscore the potential for greater consumer satisfaction through the development of bio-finished, eco-friendly naturally coloured cotton textiles